2021
DOI: 10.1136/bmjopen-2020-039211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of price and non-price policies on household cigarette consumption and nutrient intake in smoking-tolerant Indonesia

Abstract: ObjectiveTo examine the impact of cigarette price and smoking environment on allocation of household expenditure and its implication on nutrition consumption.DesignA cross-sectional study was conducted using the 2014 National Socioeconomic Survey (SUSENAS), the 2014 Village Potential Survey (PODES) and the 2013 Basic National Health Survey (RISKESDAS). SUSENAS and PODES data were collected by the Central Bureau of Statistics. RISKESDAS was conducted by National Institute of Health Research and Development (Bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…2 shows that the average protein and energy intakes for lowest quintile are far below the MoH's RDA, this signifies that increasing cigarette consumption will further attenuate poorest households in meeting the recommended dietary allowance. This is consistent with the previous study finding in Indonesian context that the increase in cigarette consumption decreases household's allocation for food spending (Djutaharta et al, 2021).…”
Section: Impact Of Cigarette Consumption On Household's Nutrition Ade...supporting
confidence: 93%
See 2 more Smart Citations
“…2 shows that the average protein and energy intakes for lowest quintile are far below the MoH's RDA, this signifies that increasing cigarette consumption will further attenuate poorest households in meeting the recommended dietary allowance. This is consistent with the previous study finding in Indonesian context that the increase in cigarette consumption decreases household's allocation for food spending (Djutaharta et al, 2021).…”
Section: Impact Of Cigarette Consumption On Household's Nutrition Ade...supporting
confidence: 93%
“…Our findings also implied that cigarette consumption has a very high opportunity cost to household's food consumption. Due to budget constraints, higher spending on cigarette will decrease food consumption, especially among poorer households (Nugent et al, 2018;Djutaharta et al, 2021). While poorer households are more sensitive to food insecurity (Yaktiworo et al, 2017), a small decrease of food expenditure could have a substantial impact on poor household nutrition adequacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with earlier research that found smoking has a negative effect on protein intake 31 . Another study also reports reduced budget allocations for eggs, milk, and meat due to increased cigarette use 32 . In other words, because of redistributing household expenses, dietary composition changes and protein intake decline.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that poor smoking households in Indonesia divert a substantial portion of an already limited resource to tobacco, reducing their dietary quantity and quality and consequently contributing to a lower nutritional intake among the smoking families. [4][5][6] Over the long run, this crowding-out effect might adversely affect human capital investment, as studies have shown that children living in smoking families in Indonesia are exposed to a higher risk of stunting. 7 The crowding-out effect of tobacco spending has been widely documented in other countries, such as India, Pakistan, Cambodia, Bangladesh, Turkey, South Africa, Zambia, Serbia and Vietnam.…”
Section: Original Researchmentioning
confidence: 99%